Control of prudential rules of microfinance in tje economic and monetary community of central Africa - (:unkn) unknown (My University, 2016)
Microfinance has evolved over the years. Insignificant until the 1990 in the Central Africa Economic and Monetary Community (CEMAC) it became the tool used by the World Bank to fight poverty. Combined with poorly codified legal context and exclusive economic policies, its development and rapid expansion was marked by lawlessness and bankruptcies with negative consequences on the economies and moral of populations and clients using microfinance institutions (MFIs).Aware of political issues and encouraged by the experts of the World Bank, the CEMAC Heads of States, sought solutions to regulate this sector by entrusting to the Banking Commission of Central Africa (COBAC) mission to build a regulatory framework and ensure supervision.Despite this regulation, the MFI failure rate remains high which suggests that there are structural flaws that undermine the applicability of the text and/or the exercise of proper supervision.From an empirical study built around sample of microfinance organisations, it is highlighted shortcomings allowing identifying appropriate strategies to address them.The study did not take into account MFI customers’ assets as a risk factor to justify the cautious regulation. This shows that MFIs have an imperfect data not adapted to group loans with joint responsibility and renewed individual loans. Therefore, it encourages focus on the regulation and supervision practices.This microfinance regulation in the CEMAC tends to conform to international prudential standards. But it turns out that it requires corrections for efficiency and effectiveness.
Keywords: African Research